(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Objective: Describe the current situation and needs of workers in private health facilities and solutions. Method: Cross-sectional descriptive research, combined use of the method of dosing and dosing; desk study combined with a field study of 543 workers in private health facilities established and not yet established trade unions in Hanoi, Ho Chi Minh and Da Nang. Result: in 2019, private health facilities tended to increase by 14.5% compared to 2018, but only 0.65% of trade unions were established. Statistics of private health facilities have not been agreed upon between the Department of Health and the Confederation of Labor. Employees participating in trade union organizations benefit more than workers in organizations that have not participated in trade unions on social insurance, health insurance, accident insurance and toxic benefits and liability benefits. Of the interviewees 74.9% wanted workers’ representative organizations to better protect workers; 71.9% said they did not want an organization representing non-union workers in private health facilities and 22.7% did not know their position or views. Regarding the method of gathering trade union members, more than 70% of the candidates said that they must combine two methods from the bottom up and from the top down. Conclusion: the innovation of the method of gathering workers in private health facilities is an urgent requirement for trade unions at all levels.